UKRAINE-NATO RELATIONS IN THE CONTEXT OF THE IMPLEMENTATION OF THE MULTI-VECTOR MODEL OF UKRAINE'S FOREIGN POLICY (1994–2004) - PRYDUN, Stepan (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2023)
Abstract. The article analyzes the peculiarities of cooperation and political dialogue between Ukraine and the North Atlantic Treaty Organization during the presidency of L. Kuchma (1994–2004). The role and significance of relations with the Alliance in the context of the implementation of the multi-vector model of Ukraine's foreign policy course have been determined. The attempt of the Ukrainian authorities to balance between the global West and russia, the difference between the declared course of rapprochement with the Alliance and the realities of domestic and foreign political development of Ukraine is outlined.